Ta’lim Al-Lughah Al ‘Arabiyyah fi ‘Asr Al-Thabiiy Al-Jadid fi Dhau’ Al-Ta’lim Al-Mudmaj - Rahayu, Puji (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2022)
The learning process cannot be separated from the presence of the teacher. The role of the teacher in the learning process is the very dominant decisive factor in education in general, because the teacher plays a role in the learning process, where the learning process is the core of the educational process. During this pandemic, learning cannot take place face to face. In order to conduct distance learning online and offline, the choice of learning methods is very important because it will have an impact on the smooth implementation of learning. One method that can be used is the "blended learning" learning model. Blended learning is learning that combines face-to-face learning (traditional learning: lecture, assignment, question-and-answer, demonstration methods), and online learning through the use of different media and technology to support independent learning and provide learning experiences for students. Blended learning can be interpreted as a learning process that uses different approaches. The approach taken can use a variety of media and technology. Elements of blended learning-based learning combines face-to-face learning and e-learning that contains 6 (six) elements, namely: (1) face-to-face, (2) independent learning, (3) applications, (4) lessons, (5) cooperation, and (6) evaluation. Ù„Ø§ ÙŠÙ…ÙƒÙ† ÙØµÙ„ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù… Ø¹Ù† ÙˆØ¬ÙˆØ¯ Ø§Ù„Ù…Ø¹Ù„Ù…ØŒ ÙØ¯ÙˆØ± Ø§Ù„Ù…Ø¹Ù„Ù… ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù… Ù‡Ùˆ Ø§Ù„Ø¹Ø§Ù…Ù„ Ø§Ù„ØØ§Ø³Ù… Ø§Ù„Ù…Ù‡ÙŠÙ…Ù† Ù„Ù„ØºØ§ÙŠØ© ÙÙŠ Ø§Ù„ØªØ¹Ù„ÙŠÙ… Ø¨Ø´ÙƒÙ„ Ø¹Ø§Ù…ØŒ Ù„Ø£Ù† Ø§Ù„Ù…Ø¹Ù„Ù… ÙŠÙ„Ø¹Ø¨ Ø¯ÙˆØ±Ù‹Ø§ ÙÙŠ Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù…ØŒ ØÙŠØ« ØªÙƒÙˆÙ† Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„Ù… Ù‡ÙŠ Ø¬ÙˆÙ‡Ø± Ø§Ù„Ø¹Ù…Ù„ÙŠØ© Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ©. Ø®Ù„Ø§Ù„ Ù‡Ø°Ø§ Ø§Ù„ÙˆØ¨Ø§Ø¡ØŒ Ù„Ø§ ÙŠÙ…ÙƒÙ† Ø£Ù† ÙŠØªÙ… Ø§Ù„ØªØ¹Ù„Ù… ÙˆØ¬Ù‡Ù‹Ø§ Ù„ÙˆØ¬Ù‡. Ù…Ù† Ø£Ø¬Ù„ Ø¥Ø¬Ø±Ø§Ø¡ Ø§Ù„ØªØ¹Ù„Ù… Ø¹Ù† Ø¨Ø¹Ø¯ Ø¹Ø¨Ø± Ø§Ù„Ø¥Ù†ØªØ±Ù†Øª ÙˆØºÙŠØ± Ù…ØªØµÙ„ØŒ ÙŠØ¹Ø¯ Ø§Ø®ØªÙŠØ§Ø± Ø·Ø±Ù‚ Ø§Ù„ØªØ¹Ù„Ù… Ø£Ù…Ø±Ù‹Ø§ Ù…Ù‡Ù…Ù‹Ø§ Ù„Ù„ØºØ§ÙŠØ© Ù„Ø£Ù†Ù‡ Ø³ÙŠÙƒÙˆÙ† Ù„Ù‡ ØªØ£Ø«ÙŠØ± Ø¹Ù„Ù‰ Ø§Ù„ØªÙ†ÙÙŠØ° Ø§Ù„Ø³Ù„Ø³ Ù„Ù„ØªØ¹Ù„Ù…. Ø¥ØØ¯Ù‰ Ø§Ù„Ø·Ø±Ù‚ Ø§Ù„ØªÙŠ ÙŠÙ…ÙƒÙ† Ø§Ø³ØªØ®Ø¯Ø§Ù…Ù‡Ø§ Ù‡ÙŠ Ù†Ù…ÙˆØ°Ø¬ Ø§Ù„ØªØ¹Ù„Ù… "Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ø¯Ù…Ø¬". Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ø¯Ù…Ø¬ Ù‡Ùˆ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ø°ÙŠ ÙŠØ¬Ù…Ø¹ Ø¨ÙŠÙ† Ø§Ù„ØªØ¹Ù„Ù… ÙˆØ¬Ù‡Ø§Ù‹ Ù„ÙˆØ¬Ù‡ (Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„ØªÙ‚Ù„ÙŠØ¯ÙŠ: Ø§Ù„Ù…ØØ§Ø¶Ø±Ø© ÙˆØ§Ù„ØªØ¹ÙŠÙŠÙ† ÙˆØ§Ù„Ø£Ø³Ø¦Ù„Ø© ÙˆØ§Ù„Ø£Ø¬ÙˆØ¨Ø© ÙˆØ·Ø±Ù‚ Ø§Ù„Ø¹Ø±Ø¶ Ø§Ù„ØªÙˆØ¶ÙŠØÙŠ)ØŒ ÙˆØ§Ù„ØªØ¹Ù„Ù… Ø¹Ø¨Ø± Ø§Ù„Ø¥Ù†ØªØ±Ù†Øª Ù…Ù† Ø®Ù„Ø§Ù„ Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„Ø¥Ø¹Ù„Ø§Ù… ÙˆØ§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§ Ø§Ù„Ù…Ø®ØªÙ„ÙØ© Ù„Ø¯Ø¹Ù… Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ø³ØªÙ‚Ù„ ÙˆØªÙˆÙÙŠØ± Ø§Ù„Ø®Ø¨Ø±Ø§Øª Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ù„Ù„Ø·Ù„Ø§Ø¨. ÙŠÙ…ÙƒÙ† ØªÙØ³ÙŠØ± Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ø¯Ù…Ø¬ Ø¹Ù„Ù‰ Ø£Ù†Ù‡ Ø¹Ù…Ù„ÙŠØ© ØªØ¹Ù„Ù… ØªØ³ØªØ®Ø¯Ù… Ù…Ù†Ø§Ù‡Ø¬ Ù…Ø®ØªÙ„ÙØ©. ÙŠÙ…ÙƒÙ† Ø£Ù† ÙŠØ³ØªØ®Ø¯Ù… Ø§Ù„Ù†Ù‡Ø¬ Ø§Ù„Ù…ØªØ¨Ø¹ Ù…Ø¬Ù…ÙˆØ¹Ø© Ù…ØªÙ†ÙˆØ¹Ø© Ù…Ù† Ø§Ù„ÙˆØ³Ø§Ø¦Ø· ÙˆØ§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§. ØªØ¬Ù…Ø¹ Ø¹Ù†Ø§ØµØ± Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù‚Ø§Ø¦Ù… Ø¹Ù„Ù‰ Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ø¯Ù…Ø¬ Ø¨ÙŠÙ† Ø§Ù„ØªØ¹Ù„Ù… ÙˆØ¬Ù‡Ø§Ù‹ Ù„ÙˆØ¬Ù‡ ÙˆØ§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ø¥Ù„ÙƒØªØ±ÙˆÙ†ÙŠ Ø§Ù„Ø°ÙŠ ÙŠØØªÙˆÙŠ Ø¹Ù„Ù‰ Ù¦ (Ø³ØªØ©) Ø¹Ù†Ø§ØµØ±ØŒ ÙˆÙ‡ÙŠ: (Ù¡) ÙˆØ¬Ù‡Ø§Ù‹ Ù„ÙˆØ¬Ù‡ (Ù¢) Ø§Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù…Ø³ØªÙ‚Ù„ØŒ (Ù£) Ø§Ù„ØªØ·Ø¨ÙŠÙ‚Ø§ØªØŒ (Ù¤) Ø¯Ø±ÙˆØ³ Ùˆ (Ù¥) ØªØ¹Ø§ÙˆÙ† Ùˆ (Ù¦) ØªÙ‚ÙŠÙŠÙ….